(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the level of public satisfaction with public services in the Driving License making unit at the Purworejo Police Traffic Unit. The service of making a Driver’s License is a form of public service that reflects the performance of the police in providing services to the community. This study uses a quantitative approach with the Community Satisfaction Index survey method which refers to the Guidelines for the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform No. 14 of 2017. The data was obtained through the distribution of questionnaires to 100 respondents who were users of the service of making or renewing Driver’s Licenses at the Purworejo Police. The results of the study showed that the IKM value of the Driver’s License issuance service unit was 77,944 with category "B" (Good). The element of service with the highest value is found in the handling of complaints (3,580) with the category "A" (Excellent) the element with the lowest score is the fairness of the cost (2,730) and the speed of service (3,030), both of which are in the category "C" (Adequate). These findings show that in general, the service for making Driver’s Licenses at the Purworejo Police has been running well, but there is still a need for improvement in terms of service time efficiency and cost transparency so that the quality of public services can be improved as a whole